A stromal cell population in the large intestine identified by tissue factor expression that is lost during colorectal cancer progression - Eriksson, Oskar; Asplund, Anna; Hegde, Geeta; Edqvist, Per-Henrik; Navani, Sanjay; Pontén, Fredrik; Siegbahn, Agneta (Thrombosis and Haemostasis, 2016)
Colorectal cancer (CRC) is a major cause of morbidity and mortality, and the composition of the tumour stroma is a strong predictor of survival in this cancer type. Tissue factor (TF) functions as the trigger of haemostasis together with its ligand coagulation factor VII/VIIa, and TF expression has been found in tumour cells of colorectal tumours. However, TF expression in the CRC tumour stroma or its relationship to patient outcome has not yet been studied. To address this question we developed and validated a specific anti-TF antibody using standardised methods within the Human Protein Atlas project. We used this antibody to investigate TF expression in normal colorectal tissue and CRC using immunofluorescence and immunohistochemistry in two patient cohorts. TF was strongly expressed in a cell population immediately adjacent to the colorectal epithelium. These TF-positive cells were ACTA2-negative but weakly vimentin-positive, defining a specific population of pericryptal sheath cells. In colorectal tumours, TF-positive sheath cells were progressively lost after the adenoma-to-carcinoma transition, demonstrating downregulation of this source of TF in CRC. Furthermore, loss of sheath cell TF was significantly associated with poor overall and disease-specific survival in rectal but not colon cancers. In conclusion, we demonstrate that TF is a marker of a specific cell population in the large intestine, which is lost during CRC progression. Our results highlight the role of the tumour stroma in this cancer type and suggest TF to be a potential prognostic biomarker in rectal cancers through the identification of pericryptal sheath cells.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Tissue microarray; Tissue Factor/factor VII; immunohistochemistry; biomarker; colorectal cancer